2008
DOI: 10.1007/s11103-008-9329-1
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose induction of Arabidopsis miR398 represses two Cu/Zn superoxide dismutases

Abstract: MicroRNAs (miRNAs) are approximately 21-nt RNAs that reduce target accumulation through mRNA cleavage or translational repression. Arabidopsis miR398 regulates mRNAs encoding two copper superoxide dismutase (CSD) enzymes and a cytochrome c oxidase subunit. miR398 itself is down-regulated in response to copper and stress. Here we show that miR398 is positively regulated by sucrose, resulting in decreased CSD1 and CSD2 mRNA and protein accumulation. This sucrose regulation is maintained both in the presence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
219
1
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(237 citation statements)
references
References 37 publications
11
219
1
6
Order By: Relevance
“…Thus, in vivo, slicer-deficient AGO1 mutants may be locked in a single conformational state, potentially not competent to perform all functions of the wild-type protein. In this regard, we note that the miR398 targets CSD1 and CSD2 displayed similar accumulation at the protein level in ago1-3 and in slicer-deficient seedlings, despite the fact that several studies have shown these targets to be regulated in part by translational repression (Brodersen et al, 2008;Dugas and Bartel, 2008; Li et al, Figure 5. RNA-seq analysis upon conditional loss of AGO1 function.…”
Section: Possible Pitfalls Of Use Of Slicer-deficient Mutantsmentioning
confidence: 69%
See 1 more Smart Citation
“…Thus, in vivo, slicer-deficient AGO1 mutants may be locked in a single conformational state, potentially not competent to perform all functions of the wild-type protein. In this regard, we note that the miR398 targets CSD1 and CSD2 displayed similar accumulation at the protein level in ago1-3 and in slicer-deficient seedlings, despite the fact that several studies have shown these targets to be regulated in part by translational repression (Brodersen et al, 2008;Dugas and Bartel, 2008; Li et al, Figure 5. RNA-seq analysis upon conditional loss of AGO1 function.…”
Section: Possible Pitfalls Of Use Of Slicer-deficient Mutantsmentioning
confidence: 69%
“…Nonetheless, the observation that central base pairing is required for efficient translational repression of a luciferase reporter in vitro, even when assayed with a catalytically deficient AGO1 (Iwakawa and Tomari, 2013), indicates that a requirement for central pairing in a miRNA:mRNA interaction does not necessarily imply that slicing is employed as the dominant mechanism to bring about mRNA repression. Furthermore, central complementarity is not always required for target regulation in plants (Dugas and Bartel, 2008), nor is it always sufficient, since determinants of miRNA-guided regulation can be found in sequences flanking the target site (Li et al, 2014).…”
mentioning
confidence: 99%
“…Down-regulation of miR398 by oxidative stresses leads to higher transcription of Cu/Zn superoxide dismutase1 (CSD1) and CSD2 and enhances oxidative stress tolerance in Arabidopsis (Sunkar et al, 2006). Conversely, the miR398 level is up-regulated by Suc, resulting in decreased CSD1 and CSD2 mRNA and protein accumulation (Dugas and Bartel, 2008). Here, we show that miR398b accumulation is significantly increased at 24 hpi in the susceptible line LTH and increased at 12 hpi in the resistant line IRBLkm-Ts upon M. oryzae infection (Table I; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Frozen tissue was ground using a mortar and pestle, and RNA was isolated using RNeasy Mini kits (Qiagen, Valencia, CA). Total RNA (Ϸ4 g) was electrophoresed and processed for Northern blotting as previously described (46). Digoxigenin-labeled ICL and MLS probes were amplified using a PCR DIG Probe Synthesis kit (Roche, Indianapolis, IN), according to the manufacturer's instructions, from a wild-type genomic DNA template.…”
Section: Methodsmentioning
confidence: 99%